Representasi Ageisme dalam Serial Web "55:15 Never Too Late" - Ndaru Dharma Relawan (Jurnal Ilmu Komunikasi, 2022)
Lately, the elderly often seen in negative stereotypes with all their deficiency so the elderly are always portrayed as discriminated against in popular culture products such as movies, web series and series. The problem of age discrimination must be resolved immediately because it has a negative impact on the physical and mental health of the elderly. The releases of the “55:15 Never Too Late” (2021) through YouTube channel GMMTV Thailand, appeared with a balanced main cast from two different generations (not only making young actors and actresses as the main characters). This research will use Roland Barthes's semiotic model to analyze the representations of ageism present in this web series. The results of this study show that some characters from the “55:15 Never Too” Late” web series justify the negative stereotypes inherent in the elderly, and there are also several other characters who show resistance to ageism through the level of analysis in denotation, connotation, and myth of some scenes that are believed to represent the phenomenon of ageism in the web series.